Association of a rare thyroglobulin gene microsatellite variant with autoimmune thyroid disease. - Collins, J; Heward, J; Carr-Smith, J; Daykin, J; Franklyn, J; Gough, S (2003)
Genetic and environmental factors contribute to the development of Graves' disease and Hashimoto's thyroiditis. These diseases, although clinically distinct, share many immunological and histological features. Susceptibility genes for autoimmune thyroid disease (AITD) have been investigated, although only the human leukocyte antigen and cytotoxic T lymphocyte-associated antigen-4 gene regions have been consistently associated with disease. Recent data, however, have shown linkage and association of chromosome 8q24 (containing the thyroglobulin gene) to AITD. Therefore, we performed a case-control association study on patients with AITD and controls using previously associated markers (D8S284 and Tgms2). No differences in allele frequencies were observed between AITD cases and controls for D8S284. Compared with the three common alleles (frequencies >10%), the rare alleles of Tgms2 were increased (chi(2)= 10.6; P = 0.001) at Tgms2. This group included the 336-bp allele (increased in cases vs. controls: chi(2)= 24.97; P < 0.001), which has previously been reported to be associated with AITD. The rarity of this allele in the United Kingdom, however, precluded analysis in our family dataset. Although these findings may represent a random chance event, in view of previous reports of linkage and association of this gene region to AITD, this may be an example of a rare causal variant of a complex disease.